2017
DOI: 10.1130/gsatg312a.1
|View full text |Cite
|
Sign up to set email alerts
|

Increased Land Subsidence and Sea-Level Rise Are Submerging Egypt’s Nile Delta Coastal Margin

Abstract: Egypt's Nile delta, only ~1 m above mean sea level at the Mediterranean coast, is subject to uneven rates of submergence. This is a response to several factors leading to increasing land lowering (subsidence) of the northern delta and adjacent seafloor, plus an accelerating rise in eustatic (world) sea level in the Mediterranean. An average eustatic sealevel rise of ~3 mm/yr represents only ~26% to 45% of total relative sea-level rise measured along this margin. Three factors leading to subsidence are neotecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 26 publications
(29 reference statements)
2
43
0
Order By: Relevance
“…Thus, the construction of the Dam and barrages not only control the water flow, but also the sediment load delivered to the Nile Delta. In addition, future dams such as the construction of Ethiopia's Grand Renaissance Dam (GERD) are expected to diminish Nile flow and sediment supply to Egypt's delta region even further [26].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the construction of the Dam and barrages not only control the water flow, but also the sediment load delivered to the Nile Delta. In addition, future dams such as the construction of Ethiopia's Grand Renaissance Dam (GERD) are expected to diminish Nile flow and sediment supply to Egypt's delta region even further [26].…”
Section: Discussionmentioning
confidence: 99%
“…The average vertical ground movement rate was recorded as over 4 mm/year across the Nile Delta, while the maximum rates of subsidence were estimated at the east of the Damietta promontory (the eastern down-stream branch of the River Nile). Recently, Stanley and Clemente [26] reported that the maximum subsidence rates have been estimated as 8.4 mm/year in the NE Delta. The highest subsidence velocities were attributed to the major eastern Mediterranean fault system with accelerated velocities attributed to the thick belt of Holocene sediments ( Figure 1).…”
Section: Land Subsidence In the Nile Deltamentioning
confidence: 99%
See 3 more Smart Citations